Sequential Plasma Activation for Low Temperature Bonding of Aluminosilicate Glass. (21st May 2021) - Takeuchi, Kai; Mu, Fengwen; Yamauchi, Akira; Suga, Tadatomo
Abstract : Low temperature bonding of glass materials is a focus of research and development for the fabrication and packaging of optical and microfluidic devices. In order to bond glass materials with post-bonding annealing at no more than 200 °C, surface activation by plasma treatment is effective by forming OH groups on the bonding surfaces. In this study, sequential plasma activation using O2 plasma, N2 plasma, and N radicals are investigated for components of aluminosilicate glass. The substrates of fused silica, sapphire, and aluminosilicate glass are successfully bonded by sequential plasma activation and post-bonding annealing at 200 °C. Compared to conventional plasma activation bonding using only O2 plasma, the bond strength is improved for fused silica and aluminosilicate glass, but not for sapphire. XPS analysis reveals that the sequential plasma activation including N2 plasma leads to aluminum nitrides formation in case of sapphire and aluminosilicate glass bonding, which results in a lower bond strength than fused silica. It has been demonstrated that sequential plasma activation is effective for the bonding of SiO2 by introducing unstable and reactive silicon oxynitrides at the bonding interface.